2006
DOI: 10.1002/srin.200606128
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nozzle Base Material on the Rate of Clogging during the Continuous Casting of Aluminum‐Killed Steels

Abstract: One approach to solving the problem of nozzle clogging during the continuous casting of aluminum-killed steels is through careful selection of nozzle materials. In this study, the rate of clogging was measured while casting steel through simulated nozzles produced from alumina, zirconia, magnesia, zirconia-graphite, and alumina-graphite -three common base materials and two common carbon-containing nozzle materials. Spent nozzles were characterized using optical and cathodoluminescence microscopy. Interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…The oxide phase density was set to 6500 kg m 23 , m was 350 kg and f C was calculated to be 0?34. Hence, the amount of clogging network was calculated to be 70 cm 3 . From the nozzles shown in Fig.…”
Section: Precipitation or Adhesionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxide phase density was set to 6500 kg m 23 , m was 350 kg and f C was calculated to be 0?34. Hence, the amount of clogging network was calculated to be 70 cm 3 . From the nozzles shown in Fig.…”
Section: Precipitation or Adhesionmentioning
confidence: 99%
“…2 Furthermore, it was found to be independent of whether zirconia, alumina, alumina graphite or magnesia was used as a nozzle material. 2,3 Freezing and reoxidation of the steel was also suggested as a probable clogging mechanism, and an oversized nozzle was suggested as a possible solution to decrease clogging. 2 It has also been found that steels in which a solid oxide phase is stable suffer from clogging, while steels with only liquid oxide phases do not.…”
Section: Introductionmentioning
confidence: 99%
“…To aid analysis, a clogging factor (CF) for each data point in the mass cast data was calculated per the methodology developed by Trueba. [15] The CF is a ratio of the actual mass flow rate through the nozzle at time t to the theoretical mass flow rate through the nozzle at time t based on the discharge coefficient determined from the initial mass flow through the nozzle. The mass flow rate for flow through an orifice is…”
Section: A Casting Curve Analysismentioning
confidence: 99%
“…The reasons for the clogging and the possible countermeasures to prevent clogging have been extensively studied. [1][2][3][4][5][6][7][8] Some research has been carried out to remove inclusions in molten steel during a ladle treatment as well as during a tundish operation. [9][10][11][12] However, it is impossible to obtain a completely clean steel with the current steel production technology.…”
Section: Introductionmentioning
confidence: 99%